Strategies to avoid intraoperative blood transfusion. Issue 2 (February 2016) - Hamilton, Christopher; Carroll, Craig
Abstract: Anaemia and blood transfusion are risk factors in the perioperative and critical care settings. Effective management begins pre-operatively, should be individualized to the patient and is subject to their own clinical risks. This article addresses the current evidence base for intraoperative strategies to avoid blood transfusion in these settings.